Augmented Reality Cubes for Cognitive Gaming: Preliminary Usability and Game Experience Testing - Costas Boletsis; Simon McCallum (Serious Games Society, 2016)
Early detection is important in dementia care; however, cognitive impairment is still under-recognised and under-diagnosed. Cognitive screening and training are two important preventative treatments, which can lead to early detection of cognitive decline. In this work, the "Cognitive Augmented Reality Cubes" (CogARC) system is presented, i.e. a serious game for cognitive training and screening, utilising an interaction technique based on Augmented Reality and the manipulation of tangible, physical objects (cubes). The game is a collection of cognitive mini-games of preventative nature and is, primarily, targeting elderly players (≥60 years old). A preliminary testing was conducted focusing on the game experience that CogARC offers (utilising the In-Game Experience Questionnaire), the usability of the system (using the System Usability Scale), and the specific user observations and remarks, as documented by open, semi-structured interviews.  Overall, CogARC demonstrated satisfying positive responses, however, the negative reactions indicated that there are specific problems with aspects of the interaction technique and a number of mini-games. The open interview shed more light on the specific issues of each mini-game and further interpretation of user interactions. The current study managed to provide interesting insights into the game design elements, integration of Augmented Reality, tangible interaction of the system, and on how elderly players perceive and use those interaction components.